EFEKTIVITAS PERJANJIAN BILATERAL AMERIKA SERIKAT DAN KOLOMBIA MENGENAI PEMBERANTASAN PEREDARAN NARKOTIKA ILEGAL DI AMERIKA SERIKAT (2003-2008) - Naomi Putri L.M; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study examines the extent to which the effectiveness of the agreement between the United States and Colombia to suppress illegal narcotics through the sea. this agreement was agreed with the efforts of the United States to reduce drug smuggling from Colombia, as well as overcoming the illegal narcotics trafficking in the United States. From these discussions can be drawn two variables, among others, the United States Agreement with Colombia on the eradication of illegal narcotics through the sea channel which is an independent variable. while the handling of illegal narcotics problems in the United States runs effectively, which is a dependent variable.The agreement was agreed by the Colombian government as failing to handle the increase in opium and marijuana results in its own country. it makes the two countries cooperate under an agreement. The agreement was effective. including large-scale operations for successfully seizing illegal drugs, prevention, treatment and rehabilitation for users and addicts, the ever-increasing destruction of laboratory drugs, the seizure of facilities and infrastructure that support drug trafficking, and success in cartel arrests including members and leaders .Keywords: Bilateral Agreement, Drug Enforcement Cooperation Trade, By Sea, USA and Colombia